NFKF is a synthetic fragment derived from rat hemopressin that protects mice from neurodegeneration - Heimann, Andrea S.; Giardini, A. C.; Sant'Anna, M. B.; Dos Santos, Nilton B.; Gewehr, Mayara C. F.; Munhoz, Carolina D.; Castro, Leandro M. [UNESP]; Picolo, Gisele; Remer, Ricardo A.; Ferro, Emer S. (Elsevier B.V., 2020)
Previous studies suggested the pharmacological potential of rat hemopressin (PVNFKFLSH) and its shorter synthetic peptide NFKF, to protect from pilocarpine-induced seizures in mice. Orally administered NFKF was shown to be hundred times more potent than cannabidiol in delaying the first seizure induced by pilocarpine in mice. Here, using an experimental autoimmune encephalomyelitis (EAE) model of multiple sclerosis we have shown that C57BL/6 J mice orally administrated with NFKF (500 mu g/kg) presented better EAE clinical scores and improved locomotor activity compared to saline administrated control mice. NFKF blocked the production of IL-1beta and IL-6, and has high scores binding cannabinoid type 2 receptors. Therefore, NFKF is an exciting new possibility to neurodegenerative diseases therapeutics.
Keywords: Neurodegenerative diseases; Intracellular peptides; Cannabinoid; EAE